Audio Visual Randang Paku Ikan Rangkito Sebagai Usaha Promosi - Usman, Robby; Susan (Riset Sinergi Indonesia (RISINDO), 2022)
Rangkito's Fish Paw Randang, is a well-known fish spike business in Dharmasraya Regency. However, the randang kue rangkito fish do not yet have effective promotional media, especially advertisements in the form of Audio Visual. This makes the randang kue rangkito fish unknown to people who are outside Dharmasraya Regency. Audio Visual is a medium that is currently very effective in attracting potential customers because it is easy to upload on social media platforms such as YouTube, Instagram, Facebook and so on. The basic concept in creating this Audio Visual is to highlight the potential of the product and the values possessed by the Randang Paku Ikan Rangkito business. The research method used is the method of creating Visual Communication Designs to attract the attention of the target audience.